The getting of wisdom of a school leader - McCarthy, Terence Francis (Curtin University, 2008)
This study is an interpretive narrative that seeks understanding of self as a human being and as a school leader through examining my lived experiences over seventeen years. To interpret my reflections on these experiences, I retell and interrogate my narratives and some writings of contemporary authors on leadership and on the purposes of education. I develop propositions about leadership that provide me with preliminary understandings about leading others. After listening to various professional voices heard as I participated in local, state and national professional activities Australia-wide, I am compelled though to go beyond my propositions and subject them to more intense scrutiny, drawing on the works of philosophers such as Aristotle, Plato and Aquinas, to broaden and deepen my understanding of self as a school leader. I come to a desiring of a virtuous kind of leadership that is deeply moral and ethical. This eros, this passion for understanding, provokes a turning point in my study towards looking for guidance and inspiration from various religions such as Christianity, Islam, Buddhism and Hinduism, about possibilities for wisdom and virtue in leadership. Thus, my narrative, the getting of wisdom of a school leader, releases new insights about the role of self-knowledge, love and “the good” in leading education.